FRI0149 Fifteen Years of Biological Treatment for Rheumatoid Arthritis: Data from the Italian Lorhen Registry. (9th June 2015) - Grosso, V.; Gorla, R.; Sarzi-Puttini, P.; Atzeni, F.; Pellerito, R.; Fusaro, E.; Paolazzi, G.; Rocchetta, P.A.; Favalli, E.G.; Marchesoni, A.; Caporali, R.
Abstract : Background: The role of biologic drugs (bDMARDs) in the treatment of rheumatoid arthritis (RA) has changed over time, due to increased availability, new evidences and different international recommendations. However, given their well-defined role in the treat-to-target approach, several authors found evidences of suboptimal adherence to it. Objectives: The aim of this study is to review the baseline characteristics of an Italian multicentric observational cohort of patients with RA starting a bDMARDs from 1999 to 2015. Methods: In the LORHEN registry, we identified all adult RA patients who were administered for the first time a bDMARD between 1 January 1999 and 1 January 2015. For analysis purpose, we divided the patients into three groups, according to the date of bDMARD administration: from 1999 to 2004 (Group 1), from 2005 to 2010 (Group 2) and from 2011 to May 2014 (Group 3). We performed between-groups comparisons of baseline demographics, disease characteristics and previous treatments with csDMARDs. Results: We retrieved data from 2620 RA patients from eight different rheumatologic centers. Patients in Group 2 were younger but with a mean difference of less than 2 years with other groups. Patients in Group 3 had a statistically significant lower baseline DAS28 and HAQ compared with previous time groups. DAS28 at first switch was significantly lower in Group 3. Disease duration and time before first switch did not differed significantly between groups. Conclusions: The disease activity at which rheumatologists opt for bDMARD treatment has progressively reduced over time, consistently with recommended tighter control of RA. However, most of the patients are given the first bDMARD only after years of csDMARDs, with an established disease, poorly fitting the principles of treat-to-target. Incomplete availability of bDMARDs over territory and economical concerns, in addition to incomplete adherence to international recommendations, might explain this fact. Differences in disease duration between real life patients treated with bDMARDs and those selected in the majority of clinical trials should be taken into account when applying inferences from RCTs to regular clinical practice. Disclosure of Interest: None declared